Carbon regulations, production capacity, and low-carbon technology level for new products with incomplete demand information. (1st February 2021) - Lu, Jin; Sun, Xiaochen
Abstract: This study investigates the effects of two carbon regulations on manufacturers' production capacity and low-carbon technology level for new products with incomplete demand information. As objective functions are not concave, we use the recursive method to solve the optimization problems with/without constraints. The optimal decision rules for production capacity and low-carbon technology level are derived. The theoretical results show that carbon regulations can encourage manufacturers to improve low-carbon technology level, but they limit the manufacturers' production capacity. The benefits of carbon quotas and subsidies should be considered in conjunction with manufacturers' planned capacity, as inappropriate trade or subsidy incentives may discourage firms from low-carbon innovation. The carbon cap-and-subsidy regulation increases the decision complexity. In contrast, under the carbon cap-and-trade regulation, policymakers can consider fewer elements. Numerical results show, when the carbon trading price is low, the carbon emissions under the carbon cap-and-subsidy regulation is reduced, but there may be a high subsidy cost for policymakers. However, when the carbon trading price is above a certain threshold, the carbon cap-and-trade regulation is more beneficial for policymakers. Moreover, under the carbon cap-and-trade regulation, manufacturers' decisions and social welfare are less affected by fluctuations in market demand. Highlights: The effects of carbon regulations on manufacturers' production capacity and low-carbon technology level are investigated. The decision on low-carbon technology level is introduced into the newsvendor model with incomplete demand information. The recursive method is employed to solve joint optimization problems. Decision rules on the production capacity and the low-carbon technology level are derived.